Evaluating the impact of electrode planes on regional lung function assessment - Sang, Ling; Sun, Yutao; Lu, Yu; Lin, Zhimin (Frontiers in Physiology, 2024)
Objective: The aim of the study was to explore the influence of measurement plane on regional lung function assessed with electrical impedance tomography (EIT).Methods: Forced vital capacity (FVC) maneuver was performed in 30 lung healthy male volunteers prospectively. Simultaneously, EIT measurements were conducted at the 3 th , the 4 th and the 5 th intercostal spaces (ICS), respectively. The EIT-based spirometry parameters are calculated in a similar manner to their original definitions. Spatial and temporal distribution of the corresponding functional images were assessed and compared among the measurement planes.Results: All subjects but one were able to perform FVC maneuver according to the guidelines. Significant differences were found in 67% (6 out of 9) of the EIT-based parameters assessing the spatial and temporal distribution. The fEIT images were most homogeneous at ICS 4 compared to other two measurement planes, except for the time required for 75% of FVC. The fEIT image FVCEIT distributed towards dorsal regions when the measurement planes moved from ICS 3 to ICS 5, whereas the identified lung areas became smaller.The spatial and temporal distribution of regional lung function measured with EIT was influenced by the measurement planes. We recommend adhering to the same measurement plane for before-after comparison. ICS 4 was recommended for the sitting subjects performing lung function testing.